On-farm quality assurance in the redmeat industry of Australia - Kennedy, Anna (Curtin University, 2006)
A series of on-farm quality assurance schemes for red meat producers across Australia were developed in the late 1990s in response to increasing global demands for greater accountability within the whole food. The Cattlecare and Flockcare schemes were introduced in 1996 and 1998, respectively, to provide mechanisms for producers to demonstrate that their livestock were free of potential chemical residues, and that they had taken measures to prevent injury or stress to livestock. These schemes were independently audited codes of practice. After several years there was some dissatisfaction with the levels of adoption of these schemes, especially Flockcare. By 2001 just over 5% of all cattle producers and just over 1% of all sheep producers had implemented on-farm quality assurance. This covered nearly 16% of all cattle and 2% of all sheep in Australia, indicating that the larger than average producers were implementing quality assurance. Based on previous studies and anecdotal evidence that there were few current benefits for producers, the aims of this study were to identify the reasons for slow uptake and to quantify factors affecting implementation of on-farm quality assurance in the red meat industry. Surveys of "adopters" and "nou-adopters" of these schemes were developed and implemented in 2000 and 2001. Producers were approached initially by phone and given the options of completing the survey over the phone, by mail or by fax.Three hundred and forty-seven Cattlecare producers (9% of all certified Cattlecare producers) and 142 Flockcare producers (22% of certified Flockcare producers) across Australia were initially approached. A total of 382 adopter surveys were completed. The level of interest from adopters was remarkable, with a 75% completion rate from telephone approaches and only 9 direct refusals. These producers had over 1.3 million cattle and 0.9 million sheep covered by quality assurance schemes. This represented 5% of the total cattle population (27% of certified cattle) and less than 1% of all sheep (26% of certified sheep) in Australia at that time. There was an extremely large variation in the size of properties surveyed, which reflected the structure of the industry. The producers were asked about what motivated them to implement quality assurance, what were the problems, where could it be improved, how much time and money had they invested specifically into implementing quality assurance, what benefits had they gained (financial and other), how it had changed their management or product offered for sale, and their opinion on various issues associated with quality assurance and food safety. In addition 133 non-adopter surveys were also completed to provide a control data set. These producers had over 0.12 million cattle and 0.48 million sheep on their properties. In general, it was much harder to persuade these producers to participate. It was estimated that about 60% of producers approached refused to participate. These producers were asked similar questions; except that they were asked to estimate (if they could) how much time and money it would take to implement quality assurance. Unfortunately, most of these producers were uninterested or knew little about quality assurance and were reluctant to estimate these values, so the data for these producers was very limited.Analysis of the adopter data indicated the adoption rates between regions and schemes were significantly different. A benefit cost analysis was completed for the adopters based on estimated time and money invested into quality assurance and the tangible benefits gained from selling certified animals. The resulting net benefits were calculated as annual equivalent annuities. Only about 30% of adopters had gained any tangible benefit, and only half of these (15% of the total analysed producers) had a positive net benefit, and these were all cattle producers. Description of time, effort and money spend by adopting producers was most representative using median values due to the extreme data from some producers. Overall, implementation took a median of 13 days in the initial year and 6 days in subsequent years per property, and the median cost was $1,200 in the initial year and $500 in subsequent years. This investment of time and money equated to a median cost of $875 per year. The median net financial loss per year from adopting quality assurance was $660 per property or $2 per 100 DSE of livestock managed. Producers indicated that they were implementing quality assurance to gain financial and market benefits; but, with only 15% of producers gaining a positive net benefit, some producers were disappointed with the schemes. However they did report improvements in product (15% of producers) or management practices (90% had at least one).Improvements in product included livestock were free from chemical residues, cattle were dehorned and yards had been improved so bruising was reduced. Improvements in management practices included improved record keeping, chemical control and livestock handling. While producers mostly believed it was the right thing to do for the industry, they indicated that they would need to be rewarded for their efforts at some stage. Adopters and non-adopters had different motives for implementing quality assurance. Peer pressure, market advantage and increased returns (27%, 26% and 18% of producers, respectively) were cited as the three major prompts for adopters. All the other categories of reasons for adoption were not business-based, but more emotional. Non-adopters, however, cited increased returns, market advantage and supply chain pressure (44%, 7% and 6%, respectively) as possible prompts to implement quality assurance. Difficulties in adoption actually experienced by adopters were also different to the difficulties anticipated by non-adopters. Paperwork, actually getting to implementing it and the extra time demands (19%, 13% and 12%, respectively) were the major difficulties for adopters, while time, in costs and paperwork (19%, 16% and 12%, respectively) were the anticipated difficulties for non-adopters.Twenty-four percent of adopters had not had any difficulties, while 16% of non- adopters anticipated no difficulties. Simplification of initial paperwork, increased demand for quality assured livestock and a need to promote the schemes and the associated benefits to producers were the three highest ranking categories of suggested improvements by adopters. Non-adopters indicated similar issues but in a different order - a need to promote the schemes and the associated benefits to producers, simplification of initial paperwork and the process of implementation. Grouping producers based on inputs, attitudes, investment or any combination of these indicators failed to provide a statistically significant prediction of the net benefit or loss for a new adopter. The only way to identify or predict which producers would gain a positive net benefit was to focus on the methods of selling livestock. Selling direct to processors either over the hook, with forward contracts or privately appeared to be the only way to gain financial benefits from implementing quality assurance on-farm.